2000
DOI: 10.1038/81656
|View full text |Cite
|
Sign up to set email alerts
|

The human Rhesus-associated RhAG protein and a kidney homologue promote ammonium transport in yeast

Abstract: The Rhesus blood-group antigens are defined by a complex association of membrane polypeptides that includes the non-glycosylated Rh proteins (RhD and RhCE) and the RHag glycoprotein, which is strictly required for cell surface expression of these antigens. RhAG and the Rh polypeptides are erythroid-specific transmembrane proteins belonging to the same family (36% identity). Despite their importance in transfusion medicine, the function of RhAG and Rh proteins remains unknown, except that their absence in Rh(nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
303
3
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(327 citation statements)
references
References 26 publications
15
303
3
6
Order By: Relevance
“…A recent study also identified RhBG and RhCG as having a cell specific, axially heterogeneous and polarized expression in the gastrointestinal tract [13]. As is the case for RhAG, ammonium transport activity of RhCG was first shown by complementation studies in yeast [5] and then confirmed by functional studies in Xenopus oocytes [14]. RhBG-mediated ammonium transport was also recently demonstrated in the Xenopus oocyte expression system [15,16].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent study also identified RhBG and RhCG as having a cell specific, axially heterogeneous and polarized expression in the gastrointestinal tract [13]. As is the case for RhAG, ammonium transport activity of RhCG was first shown by complementation studies in yeast [5] and then confirmed by functional studies in Xenopus oocytes [14]. RhBG-mediated ammonium transport was also recently demonstrated in the Xenopus oocyte expression system [15,16].…”
Section: Introductionmentioning
confidence: 92%
“…In RBCs (red blood cells) RhCE, RhD and RhAG constitute the core of the Rh-membrane complex, the carrier of the Rh bloodgroup antigens [3,4]. Genetic complementation studies in Mepdeficient yeast provided the first experimental evidence for a direct role of RhAG in ammonium transport [5]. RhAG-dependent ammonium transport in a heterologous system was subsequently demonstrated in injected Xenopus oocytes [6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[5][6][7] The erythrocyte Rh blood group proteins are well known because of their importance in blood transfusion, but recent functional studies and structural modeling reveal that the Rh blood group proteins are members of an ancient family of proteins involved in ammonia transport. [8][9][10][11] Non-erythroid Rh proteins have now been found in other tissues including the kidney, liver, brain, and skin 12-15 , in locations where ammonia production and elimination occurs. The family of Rh proteins has now been expanded significantly through comparative genomics and structure-function studies that reveal the presence of Rh homologs in all domains of life.…”
Section: Introductionmentioning
confidence: 99%
“…The RhD, RhCE, and RhAG proteins form a heteromeric, most likely heterotrimeric, complex but only RhAG has been shown to function in ammonium transport [27,48]. RhD and RhCE differ in some otherwise highly conserved pore residues.…”
Section: Rh-mediated Ammonia Transport In Animal Cellsmentioning
confidence: 99%